Risk factors for infection following prostate biopsy - a case control study. Issue 1 (December 2015) - Anderson, Elliot; Leahy, Olivia; Cheng, Allen; Grummet, Jeremy
Abstract Background Infection is a complication of TRUS prostate biopsy, despite the use of antimicrobial prophylaxis. Worryingly the rate of infectious complications following TRUS biopsy has been shown to be increasing. We aimed to determine the rate, severity, risk factors, standard patterns of care and microbiology resistance profiles associated with TRUS biopsy sepsis. Methods A retrospective case–control study was conducted. Using electronic coding all patients who presented to Cabrini Hospital with sepsis following a TRUS biopsy from 2009 to 2013 were identified. Validated cases were matched to controls in a ratio of 1:3. Eligible controls were required to have undergone a TRUS biopsy at the same surgical institution as the case and in the closest period of time. Demographic, procedural and patient related data-points were recorded for all patients using hospital and urologist records. Univariate logistic regression models were constructed and used to determine risk factors associated with infection. Results 71 cases developed sepsis following TRUS biopsy and were matched to 213 controls. The average rate of sepsis over the 5-year study period was 1.5 %. A SOFA score ≥ 2 was identified in 28 % of cases. We found a high prevalence of antimicrobial resistant E. coli, with 61 % of blood culture isolates classified as Multidrug resistant organisms. Eight different prophylactic antimicrobial regimens were identified with 33 % of cases receiving ineffective antimicrobial prophylaxis. Statistically significant risk factors included previous antimicrobial use and prior international travel within the six months prior to biopsy. Conclusions TRUS biopsy is an elective procedure and as such needs to be associated with minimal morbidity. The patterns of care surrounding periprocedural variables for TRUS biopsies were non-uniform and diverse. A wide variety of different prophylaxis regimens and bowel preparation routines were recorded. Patients with risk factors for sepsis may represent a better target population for intervention with alternative preventative strategies. Alternative preventative options include augmented prophylaxis, tailored prophylaxis or the TP biopsy approach either as a first line biopsy modality or based on epidemiological risk factors.